Tailoring the rheology and electrical properties of polyamide 66 nanocomposites with hybrid filler approach: graphene and carbon nanotubes. Issue 9 (4th March 2021) - Palacios, Jordana K; Ben Fekih, Achraf; Yus Argon, Cristina; Irusta, Silvia; Jestin, Simon; Dagréou, Sylvie
Abstract: The aim was to improve the processability and reduce the melt viscosity of well‐known nanocomposites based on polyamide 66 (PA66) and carbon nanotubes (CNT), while keeping the good electrical conductivity gained after the addition of CNT. Thus, a nanocomposite based on PA66 as the thermoplastic matrix and 3% of CNT was selected. At this composition, a percolated network is created and the material is electrically conductive. The approach followed was the addition of graphene nanoplatelets (GNP) of two different lateral sizes to obtain a PA66 nanocomposite with hybrid filler: CNT/GNP. In addition, a third nanocomposite of PA66 with GNP only was prepared for comparison purposes. The rheological characterization determined that adding 1% of GNP of 2 μm particle size decreased the viscosity of the system by 87%. However, the electrical conductivity was diminished to some extent, from 10 −5 to 10 −9  S cm −1 approximately. The Cross rheology model described successfully the experimental rheological data. The CNT/GNP nanocomposite exhibited faster relaxations, almost four orders of magnitude, in comparison with the CNT nanocomposite but slower than the GNP nanocomposite. The nanoparticles improved the crystallization ability of PA66 acting as nucleating agents and increasing the PA66 crystallization temperature by almost 10 °C. Self‐nucleation experiments demonstrated a supernucleation feature of the hybrid filler. The nucleation efficiency was about 500%. © 2021 Society of Chemical Industry Abstract : PA66 nanocomposites with better rheological behavior, lower viscosity and improved electrical conductivity and crystallization are possible with a hybrid filler approach: the combined addition of graphene and carbon nanotubes.